Survey of Ehrlichia and Anaplasma species in white tailed deer and in ticks by real-time RT-PCR/PCR and DNA sequencing analysis - Katragadda, Chakravarthy (Kansas State University, 2011)
Ehrlichia and Anaplasma species are rickettsial organisms which infect a variety of mammalian species. The organisms are transmitted from ticks and are maintained in reservoir hosts. Several pathogens have been identified in recent years as the causative agents for emerging infections in people. One of the primary reservoir hosts for the pathogens is the white tailed deer. In this study, 147 deer blood samples and 37 ticks were evaluated for the prevalence of Ehrlichia/Anaplasma species by TaqMan-based real time amplification assay and DNA sequence analysis. One hundred and thirteen (74%) samples tested positive with the Ehrlichia/Anaplasma genera-specific probe. Further analysis of the samples with the probes specific for human ehrlichiosis agents, E. chaffeensis and E. ewingii identified 4 (2.7%) and 7 (4.7%) positives, respectively. Test positives from 24 randomly selected samples were further evaluated by sequence analysis targeting to a 450 bp segment of 16S rRNA gene. All 24 samples were confirmed as positive for the Ehrlichia GA isolate # 4 (GenBank #U27104.1). DNAs from 37 pools of ticks collected from the white tailed deer were also evaluated. The TaqMan-based real time PCR assay with Anaplasma/Ehrlichia common probe identified 29 (78%) tick pools as positives whereas E. chaffeensis- and E. ewingii-specific probes identified three (8%) and one (3%) positives, respectively. The PCR and sequence analysis of tick samples identified Gram-negative bacteria species which included one endosymbiont of Rickettsia species (one tick pool), one Alcaligenes faecalis strain (three tick pools), five different Pseudomonas species (9 tick pools) and five different uncultured bacteria organisms (7 tick pools). Although the pathogenic potential of the white-tailed deer isolates of Anaplasma and Ehrlichia agents remains to be established, their high prevalence and the presence of human ehrlichiosis pathogens in white-tailed deer is similar to earlier findings. The high prevalence of the deer isolates of Anaplasma and Ehrlichia species demonstrates the need for further assessment of the pathogenic potential of these organisms to people and domestic animals.
Keywords: Ehrlichia species; Anaplasma species; Real-time PCR; DNA sequencing; White-tailed deer and ticks; Vertebrate hosts and vectors; Epidemiology (0766); Molecular Biology (0307); Veterinary Medicine (0778)